2005
DOI: 10.1038/sj.onc.1208547
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet irradiation-induced K+ channel activity involving p53 activation in corneal epithelial cells

Abstract: Recent studies from our lab found that ultraviolet (UV) irradiation induces a voltage-gated potassium (Kv) channel activation and subsequently activates JNK signaling pathway resulting in apoptosis. The present study in rabbit corneal epithelial (RCE) cells is to investigate mechanisms of UV irradiation-induced Kv channel activity involving p53 activation in parallel to DNA damage-induced signaling pathway. UV irradiationinduced signaling events were characterized by measurements of JNK activation and further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
3
22
0
Order By: Relevance
“…UV irradiationinduced p53ser15 phosphorylation (within 5-15 min) occurs earlier than the site of p53ser20 (in 30 min). These data are consistent to the results obtained from Western analysis of this protein (Wang et al, 2005). Immunostaining experiments reveal that UV irradiation increases phosphorylation of p53ser15 in the nuclei in 15 min, but total p53 protein levels are not changed in control cells (Fig.…”
Section: Uv Irradiation-induced Activation Of P53 In Corneal Epithelisupporting
confidence: 91%
See 4 more Smart Citations
“…UV irradiationinduced p53ser15 phosphorylation (within 5-15 min) occurs earlier than the site of p53ser20 (in 30 min). These data are consistent to the results obtained from Western analysis of this protein (Wang et al, 2005). Immunostaining experiments reveal that UV irradiation increases phosphorylation of p53ser15 in the nuclei in 15 min, but total p53 protein levels are not changed in control cells (Fig.…”
Section: Uv Irradiation-induced Activation Of P53 In Corneal Epithelisupporting
confidence: 91%
“…However, TNF-α suppresses particular types of K + channel activity in other cell types, indicating that the effect of TNF-α on K + channel activity is dependent on the channel type and cell origins (Vicente et al, 2004;Wang J et al, 2004). In corneal epithelial cells, TNF-α does not induce apoptosis, but instead it increases the expression of p21 resulting in cell cycle attenuation in the G 1 phase (Wang et al, 2005). We, as well as others, in numerous earlier studies have shown that K + channel activity is the major conductance in the cell membrane.…”
Section: K + Channel Activity Evoked By Tnf-αmentioning
confidence: 57%
See 3 more Smart Citations